The Development of a Tutor Manual for Year One Anatomy and Physiology Teaching Assistants - Talman, Marianne (My University, 1988)
A "Tutor Manual" was developed to facilitate the small group learning experience in the laboratory and tutorial component of the introductory Anatomy and Physiology Nursing course at McMaster University. The manual included a comprehensive discussion of the information and important concepts in the laboratory and tutorial sessions, and provided guidelines on how to facilitate the group effectively in its consideration of the topics. Theoretical educational concepts were considered in the development of this manual, including: lifelong learning; principles of adult learning; the use of small-group discussion in teaching and learning; the role of the facilitator: and the use of objectives.
The Development of an Anatomy and Physiology Tutor Manual
Keywords: tutor manual; anatomy; physiology; teaching assistants